ANALYSIS OF FACTORS WHICH AFFECTING THE ECONOMIC GROWTH - Suparna Wijaya (Jurnal Ekonomi dan Studi Pembangunan, 2017)
High economic growth and sustainable process are main conditions for sustainability of economic country development. They also become measures of the success of the country's economy. Factors which tested in this study are economic and non-economic factors which impacting economic development. This study has a goal to explain the factors that influence on macroeconomic Indonesia. It used linear regression modeling approach. The analysis result showed that Tax Amnesty, Exchange Rate, Inflation, and interest rate, they jointly can bring effect which amounted to 77.6% on economic growth whereas the remaining 22.4% is the influenced by other variables which not observed in this study.Keywords: tax amnesty, exchange rates, inflation, SBI and economic growthJEL Classification: O23, O40